1983
DOI: 10.1021/jm00356a028
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of esters of phosphonoformic acid and their antiherpes activity

Abstract: Aliphatic and aromatic mono-, di-, and triesters of phosphonoformic acid (foscarnet) were synthesized. The triesters were prepared by the Michaelis-Arbuzov reaction and were hydrolyzed to di- and monoesters. The compounds were tested for antiviral activity on isolated herpes simplex virus type 1 (HSV-1) DNA polymerase, in a HSV-1 plaque reduction assay, and on a cutaneous HSV-1 infection in guinea pigs. None of the esters inhibited the activity of isolated HSV-1 polymerases. Monoesters with a free carboxylic g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

1983
1983
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 1 publication
(1 reference statement)
1
33
0
Order By: Relevance
“…With respect to this aim, several lipophilic mono-, di-and triester prodrugs ofPFA ( Fig. 1) have been synthesized previously (Noren et al, 1983;Vaghefi et al, 1986;Griengl et al, 1988;Lambert et al, 1989;Iyer et al, 1989Iyer et al, , 1994Neto et al, 1990;Rosowsky et al, 1990;Saha et al, 1991;Charvet et al, 1994;Walker et al, 1994;Hostetler et al, 1996;Briggs et al, 1996). One of the major limitations ofthis approach is the high instability towards chemical hydrolysis of simple alkyl or aryl PFA triester prodrugs, which leads primarily to a P-C bond scission at physiological pH (Krol et al, 1991;Krol & Thatcher, 1993;Mitchell et al, 1991Mitchell et al, , 1992.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to this aim, several lipophilic mono-, di-and triester prodrugs ofPFA ( Fig. 1) have been synthesized previously (Noren et al, 1983;Vaghefi et al, 1986;Griengl et al, 1988;Lambert et al, 1989;Iyer et al, 1989Iyer et al, , 1994Neto et al, 1990;Rosowsky et al, 1990;Saha et al, 1991;Charvet et al, 1994;Walker et al, 1994;Hostetler et al, 1996;Briggs et al, 1996). One of the major limitations ofthis approach is the high instability towards chemical hydrolysis of simple alkyl or aryl PFA triester prodrugs, which leads primarily to a P-C bond scission at physiological pH (Krol et al, 1991;Krol & Thatcher, 1993;Mitchell et al, 1991Mitchell et al, , 1992.…”
Section: Introductionmentioning
confidence: 99%
“…It fIlows that the esters undergo hydrolysis (probably by non-.specific esterases) following entry to the cell. Presumably they would more readily traverse the cell membrane, followed by enzymatic release of PFA, but none of them was more effective than the parent PFA (45). It had previously been found that phos-.…”
Section: Pyrophosphate Analoguesmentioning
confidence: 99%
“…Hence at physiological pH PAA is appreciably less charged than PFA (in fact PAA is almost entirely in the form of the disodium salt, whereas 50% of PFA is the trisodium salt), and this may account in part for the observed differences in activity between the two. Aliphatic and aromatic mono.-, di-and triesters of PPA have been prepared and their activities examined (45). None of them inhibited HSV.-1 DNA polymerase in vitro.…”
Section: Pyrophosphate Analoguesmentioning
confidence: 99%
“…6,7 Because of its multiple negative charges at physiological pH, PFA has low oral bioavailability; this poor ability to penetrate cell membranes has long been a major impediment to its overall effectiveness as an anti-viral drug. 8,9 Past efforts to address this shortcoming by prodrug strategies have included partial esterification of PFA, 8À13 including its incorporation into cyclic esters, 11 and the replacement of an oxygen atom in PFA by a sulfur atom. 14À16 It has been shown that all three acidic groups of PFA must be available for maximal nucleic acid polymerase inhibition activity, and thus the ultimate antiviral activity of PFA prodrugs wherein one or more of these groups has been derivatized by esterification (or amidation) is likely to depend on a hydrolytic activation process in vivo to release the active drug.…”
mentioning
confidence: 99%
“…14À16 It has been shown that all three acidic groups of PFA must be available for maximal nucleic acid polymerase inhibition activity, and thus the ultimate antiviral activity of PFA prodrugs wherein one or more of these groups has been derivatized by esterification (or amidation) is likely to depend on a hydrolytic activation process in vivo to release the active drug. 8 Thus, PFA-amino acid conjugates might be useful as prodrugs of foscarnet, provided that such compounds are synthetically accessible and facile cleavage of the PFA-amino acid linkage occurs in vivo. It was recently reported that a fully alkyl-protected, neutral P-N linked PFA-amino acid phosphoramide produced by coupling (MeO)(Cl)P(O)CO 2 Me with an l-amino acid Et ester, decomposed with P-C cleavage under basic deprotection conditions.…”
mentioning
confidence: 99%